Establecimiento y producción de materia seca de gramíneas promisorias en el departamento de Jutiapa, Guatemala - Reyes A., Sergio (2016)
With the aim of sclecting improved pasture grasses for the sub-humid forcst conditions in the department of Jutiapa, Guatemala, Courteen acccssions previously selected wercevaluated. A split plot randomized complete block design with four replications was used where the main plots were accessions and sub plots cutting frequency (3,5,7 and 9 weeks). Measurements were made during the periods of maximum and minimum precipitation in 1988 and 1989. Mean ground cover was 82.9% ± 8.15 and 72.5% ± 8.34 for maximum and minimum precipitation periods, respectively. Significant (P<0.01) effects of year, precipitation period, accession, cutting frequency and interactions between these variables werc found for dry matter production. The average yield under maximum precipitation was 4.3 ton/ha with B. Dictyoneura, and 6.63 ton/ha for CIAT 6133, both of which being significantly better than the other materials (P ≤ 0.05). Under minimum precipitation, cutting frequencies of 7 and 9 wceks were equal or superior to 3 and 5 weeks, with mean yield of 4.92 t / ha. Entries B. decumbens CIAT 606, P. maximun CIAT 673, P. maximun (local), and P. purpureum cv. Mott were modcrately affected by insects. The entries P. maximun (local) and C. nlemfuensis EAP 138 showed moderate damage by discase.